2020
DOI: 10.48082/espacios-a20v41n42p02
|View full text |Cite
|
Sign up to set email alerts
|

Effect Covid-19: Burnout on nurse

Abstract: This study aims to determine the impact of the Covid-19 pandemic on burnout experienced by nurses at Dr. Hospital. Wahidin Sudirohusodo as one of the special hospitals that treat patients affected by Covid-19. This research is a qualitative study using some literature from related articles and journals as well as the results of a discussion group forum (FGD) from nurses at Dr. Wahidin Sudirohusodo Hospital Makassar. The results showed that there was a burnout in nurses when they saw so many patients who were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 12 publications
0
9
0
4
Order By: Relevance
“…Drastic changes in work environments and stress are likely deleterious to clinicians' longitudinal health outcomes [ 4 ]. Investigators outside the US assert clinicians will experience both adverse physical and psychological effects from providing health care during this pandemic [ 5 , 6 ]. A better understanding of the causes and sequelae of stressful clinical work environments can inform efforts to support clinicians' physical and emotional health during times of crisis.…”
Section: Introductionmentioning
confidence: 99%
“…Drastic changes in work environments and stress are likely deleterious to clinicians' longitudinal health outcomes [ 4 ]. Investigators outside the US assert clinicians will experience both adverse physical and psychological effects from providing health care during this pandemic [ 5 , 6 ]. A better understanding of the causes and sequelae of stressful clinical work environments can inform efforts to support clinicians' physical and emotional health during times of crisis.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the burnout nurses are nurses treating emergency patients (Asih & Trisni, 2015). Emergency nurses are nurses with the ability to give nursing care in the emergency room to gradually or suddenly resolve a patient's problems (Hardiyono et al, 2020).…”
mentioning
confidence: 99%
“…Due to their responsibility for human health, continual confrontation with patients[ 18 ] , performing clinical procedures, exposure to dying patients, dealing with emergency, and unpredictable situations, and exposure to too much noise at the workplace, nurses are exposed to high levels of work pressure. [ 19 20 21 ] Epidemiological studies have shown that about 17%–41% of nurses in different countries have symptoms of depression and approximately 20%–40% of them have symptoms of anxiety. [ 2 22 ] Anxiety and depression overlap with burnout.…”
Section: Discussionmentioning
confidence: 99%